2018
DOI: 10.21071/az.v0i0.3891
|View full text |Cite
|
Sign up to set email alerts
|

Les lapins nourris avec de l’amidon de manioc fermenté résidus II: enzyme supplementation

Abstract: La probabilité d’augmenter le niveau de remplacement optimale du maïs avec de l’amidon de manioc fermenté d’origine microbienne (résidus MFCSR) avec multi-enzyme supplementation en régimes de lapin a été évalué dans un arrangement factoriel 2x3 à huit semaines au procès. Bien que le gain de poids total (GTT) et le ratio de conversion d’alimentation (FCR) a significativement (P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Cyanide (0.68 mg/kg) and tannin (13.00 g/kg) was also detected in GLM. This suggests that GLM could be an important plant protein feed ingredient in livestock feeds formulation [21]. However, high fibre content and presence of cyanide and tannin could be a limiting factor to extent of GLM inclusion level because normal digestion interference by these anti-nutritional factors in animals had been reported [22,23].…”
Section: Composition Of the Gliricidia Leaf Mealmentioning
confidence: 99%
“…Cyanide (0.68 mg/kg) and tannin (13.00 g/kg) was also detected in GLM. This suggests that GLM could be an important plant protein feed ingredient in livestock feeds formulation [21]. However, high fibre content and presence of cyanide and tannin could be a limiting factor to extent of GLM inclusion level because normal digestion interference by these anti-nutritional factors in animals had been reported [22,23].…”
Section: Composition Of the Gliricidia Leaf Mealmentioning
confidence: 99%
“…Reports also stated that PCV, HB and MCH were major indices for evaluating circulating avian erythrocytes and were very significant in the diagnosis of anemia and also served as useful indices of bone marrow capacity to produce red blood cells as in mammals [21]. Nutrition also has a strong influence on the hematological traits and values of these traits are indicators of nutritional status of the animals [22,23]. [24] also reported that hematological constituents reflect the responsiveness of the animal to its environments which includes feed and feeding.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, dietary clove powder in broilers ( Mahrous et al , 2017 ) and clove oil in laying hen diets ( Şehitoğlu and Kaya, 2021 ) significantly lowered serum total cholesterol. Besides, supplementation with cinnamon, thyme, and Alchornea cordifolia leaf meal significantly decreased total cholesterol concentration in serum ( Najafi and Taherpour, 2014 ; Oloruntola et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%